A case study of how reshoring affects the quality of software development - Mirza, Amna (Student Undergraduate Research E-journal!, 2019)
The purpose of this research is to provide more insights into the consequences of reshoring on the performance of software development. A thorough understanding of the consequences of reshoring has been attained by interviewing the stakeholders of a recently reshored software development department. This research embraced a multimethod qualitative approach. The insights gained from the case indicates that software performance has been affected by reshoring. Due to reshoring, the software developers of the department are sitting next or close to each other. This results in less communication complexity, more collaboration among developers and better understanding of the end-product. These consequences did lead to a higher software quality performance (SQP). Other than that, reshoring also came along with some managerial implication, such as hiring new developers. But there is no causal relationship between reshoring and software quality performance. However, the consequences of reshoring do lead to a higher SQP.